Non-Invasive Ayurvedic Management of Cholelithiasis - A Case Study (AYUSHDHARA, 2023)
Cholelithiasis or gall stones is one of the most common diseases of biliary tree. Modern medicine majorly relies on surgical management of the disease as conservative treatment is usually futile. Although, Ayurvedic sciences has no mention of gallstones but the contextual representation of stones comes under Bastigata Ashmari (renal calculi). After thoroughly revising Ayurvedic texts, we discover that the bile secreted from gallbladder can correspond to Accha Pitta mentioned in Ayurveda due to its similarity in location and function. Case Report: A 64-year-old male patient approached with complaints of heaviness of abdomen, mild-to-moderate intermittent abdomen pain, nausea and with ultrasonography report which was suggestive of chronic cholecystitis with cholelithiasis measuring 0.44cm. Conclusion: The patient was diagnosed with Pittashmari and Ayurvedic treatment protocol was followed for approx. 2 months resulting in dissolution of stone and relief in signs and symptoms. Hence our article is a step further for understanding and pursuing conventional and non-surgical management of cholelithiasis.